Effects of Packing Densities in Plastic Bags on Survival of Larvae and Fry of Helostoma temmincki (C&V) - Siraj, Siti Shapor; Cheah, S. H.; Zainal Abidin, Aizam (1985)
Helostoma temmincki (C&V) larvae measuring 4.6 ± 0.6 mm total length were packed in plastic bags with oxygen at stocking densities of 0, 250, 500, 1000 and 1500/liter. Fry measuring 2. 0 cm ± 0.2 were similarly packed at densities of 0, 125, 250, 500 and 750/litre. The fish were observed for mortality 10 minutes, 24 hours and 48 hours after packing. The water quality parameters - temperature, dissolved oxygen, ammonia-N, dissolved carbon dioxide, pH and alkalinity - were determined at 0 hours for control bags only and for all bags at 48 hours after packing. There was no mortality in all bags 10 minutes after packing. After 24 hours, mortality of larvae packed at 500, 1000 and 1500/litre was less than 2% whereas no mortality was observed in the bags with fry. At 48 hours, mortalities of larvae were similar (P > 0.05) in all bags and were less than 2%. Mortalities of fry packed at 125, 250 and 500/litre were similar (P> 0.05) and less than 2%, whereas mortality of fry packed at 750/litre was significantly different (P < 0.05).